ITRAQ-based quantitative proteomic analysis of differentially expressed proteins in chemoresistant nasopharyngeal carcinoma. Issue 9 (2nd September 2018) - Wang, Kun; Chen, Zhen; Long, Lu; Tao, Ya; Wu, Qiong; Xiang, Manlin; Liang, Yunlai; Xie, Xulin; Jiang, Yuan; Xiao, Zhiqiang; Yan, Yahui; Qiu, Shiyang; et al.
ABSTRACT: Nasopharyngeal carcinoma (NPC) is a highly prevalent disease in Southeast Asia. The disease is typically diagnosed in the later stages, and chemotherapy resistance often causes treatment failure. To investigate the underlying mechanisms of drug resistance, we searched for chemoresistant-associated proteins in NPC and drug-resistant NPC cell lines using isobaric tags for relative and absolute quantitation combined with nano liquid chromatography-tandem mass spectrometry. The chemoresistant NPC cell lines CNE1DDP and CNE2DDP were resistant to 1 mg/L cisplatin, had resistant indexes of 4.58 and 2.63, respectively, and clearly grew more slowly than the NPC cell lines CNE1 and CNE2. Using three technical replicates, we identified 690 nonredundant proteins, 56 of which were differentially expressed in both groups of cell lines (CNE1 vs. CNE1DDP and CNE2 vs. CNE2DDP). Gene Ontology, KEGG pathway, and miRNA analyses and protein-protein interactions of differentially expressed proteins showed that proteins TRIM29, HSPB1, CLIC1, ANXA1, and STMN1, among others, may play a role in the mechanisms of chemoresistance in clinical therapy. The chemotherapy-resistant proteomic profiles obtained may allow the identification of novel biomarkers for early detection of chemoresistance in NPC and other cancers.